116 Effect of Zinc Oxide and Organic Zinc on Weanling Pig Performance. (12th April 2022) - LaRosae, Marissa N; Samuel, Ryan S; Clizer, David A
Abstract: Pharmacological levels (> 2, 000 ppm) of Zn from ZnO have been reported to enhance pig growth during the nursery phase. Alternatively, organic Zn sources added to nursery diets below pharmacological concentrations may provide similar growth performance benefits. Therefore, the objective of this study was to evaluate the effects of source and concentration of Zn on growth performance of weanling pigs. Newly weaned pigs (n = 1, 144; 21 d of age; 5.8 ± 0.1 kg BW) were stocked at 26 pigs per pen of equal sex in 44 pens in a wean-to-finish commercial research barn. Pens within similar barn location were randomly assigned to receive 1 of 4 dietary treatments applied over 4 dietary phases (PH) in a factorial arrangement: 1) Control: complex commercial nursery diet with dietary Zn at nutritional requirement 2) Control plus ZnO providing Zn at 3, 000 ppm in PH1-2, 1, 500 ppm in PH3, and removal of ZnO in PH4; 3) Control plus an organic Zn providing Zn at 100 ppm in PH1-4; 4) Control plus a combination of both ZnO and organic Zn source at the same inclusion levels as dietary treatments 2 and 3. The addition of organic Zn increased ( P < 0.01) ADFI from d 0 to 7 (175 vs. 149 g/d), but decreased ( P < 0.01) G:F (0.763 vs. 0.902) and then improved ( P < 0.01) G:F from d 7 to 14 (0.821 vs. 0.754). The addition of Zn from ZnO increased ( P < 0.05) ADG (312 vs. 290 g/d) and ADFI (428 vs 401 g/d) for the initial 28 d and improved ( P < 0.05) G:F (0.776 vs. 0.738) for the initial 21 d post-weaning, but not for the latter 14 d (28 to 42 d) of the nursery phase or overall (0 to 42 d). These results demonstrate that Zn above dietary requirement may improve early growth performance.